Collaboration of integrated child development services with self-help groups to decentralize the supply of supplementary feeding at Anganwadi Centers - Babu, Sunil; Nidadavolu, Nalini (International Food Policy Research Institute, 2014)
The Integrated Child Development Services (ICDS) program provides supplementary food to millions of women and young children in India for approximately 300 days a year at ICDS-run anganwadi centers (AWCs). In the mid-1970s, ICDS began supplying centrally procured raw commodities or processed foods to AWCs.